Exertional syncope and presyncope - McAward, K. J.; Moriarity, J. M. (The Physician and Sportsmedicine, 2005)
Physicians often see patients who have syncope or presyncope, but episodes associated with exercise are uncommon. Transient syncopal episodes usually require minimal evaluation and intervention. Most cases of exercise-associated syncope have neurocardiogenic origins and are benign, but fainting may signal a potentially fatal underlying problem. More serious causes of exertional syncope include structural cardiovascular abnormalities and cardiac arrhythmias. All physicians who care for active patients should be aware of the potential seriousness of this early warning sign and evaluate patients accordingly. Familiarity with the Bethesda guidelines will help clinicians decide when it is safe for an athlete to return to play following a syncopal episode.